Protective Efficacy of Recombinant Influenza Hemagglutinin Ectodomain Fusions - Nidhi Mittal; Nayanika Sengupta; Sameer Kumar Malladi; Poorvi Reddy; Madhuraj Bhat; Raju S. Rajmani; Koen Sedeyn; Xavier Saelens; Somnath Dutta; Raghavan Varadarajan (Viruses, 2021)
In current seasonal influenza vaccines, neutralizing antibody titers directed against the hemagglutinin surface protein are the primary correlate of protection. These vaccines are, therefore, quantitated in terms of their hemagglutinin content. Adding other influenza surface proteins, such as neuraminidase and M2e, to current quadrivalent influenza vaccines would likely enhance vaccine efficacy. However, this would come with increased manufacturing complexity and cost. To address this issue, as a proof of principle, we have designed genetic fusions of hemagglutinin ectodomains from H3 and H1 influenza A subtypes. These recombinant H1-H3 hemagglutinin ectodomain fusions could be transiently expressed at high yield in mammalian cell culture using Expi293F suspension cells. Fusions were trimeric, and as stable in solution as their individual trimeric counterparts. Furthermore, the H1-H3 fusion constructs were antigenically intact based on their reactivity with a set of conformation-specific monoclonal antibodies. H1-H3 hemagglutinin ectodomain fusion immunogens, when formulated with the MF59 equivalent adjuvant squalene-in-water emulsion (SWE), induced H1 and H3-specific humoral immune responses equivalent to those induced with an equimolar mixture of individually expressed H1 and H3 ectodomains. Mice immunized with these ectodomain fusions were protected against challenge with heterologous H1N1 (Bel/09) and H3N2 (X-31) mouse-adapted viruses with higher neutralizing antibody titers against the H1N1 virus. Use of such ectodomain-fused immunogens would reduce the number of components in a vaccine formulation and allow for the inclusion of other protective antigens to increase influenza vaccine efficacy.